The Leadership of KH. M. Hasyim Asy’ari in the Framework of Michel Foucault's Theory - Husnu, M Husnu Widadi; Mujahid Jamalul Falah; Ahmad Mutawakkkil (Tebuireng: Journal of Islamic Studies and Society, 2025)
M. Hasyim Asy'ari was one of the most influential Islamic scholars during the colonial era. He combined religious knowledge with transformative leadership in a social and political context. This study uses Michel Foucault's theory as a framework to understand the relationship between power, knowledge, and the formation of social structures. In the case of KH. M. Hasyim Asy'ari, this theory helps explain how religious knowledge can function as a means to create productive power relations. The researcher used a qualitative method with a descriptive-analytical approach based on literature studies. The research findings show that, according to Foucault's theory of power/knowledge, the religious knowledge possessed by KH. M. Hasyim Asy'ari can build a dominant power structure in society. According to Foucault's theory of power relations, power is not limited to government alone, but also involves social and community issues. For example, knowledge-based power is held by scholars, which, to some extent, can be used as a tool for political mobilization.